Hiroshima in america : - Lifton, Robert Jay (Putnam's Sons, 1955)
In a study of the impact of the use of the atomic bomb, two historians argue that information and debate about President Harry Truman's decision, in August 1945, to drop the bomb on Japan have been suppressed in order to prevent criticism of America.